Low malnutrition but high mortality: Explaining the paradox of the Lake Victoria region - Johannes Gräb; Jan Priebe (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2009)
Exploiting DHS data from 235 regions in 29 Sub-Saharan Africa countries, we find that the combination of low levels of malnutrition together with dramatically high rates of mortality, encountered in Kenya's Lake Victoria territory, is unique for Sub-Saharan Africa. This paper explores the causes of this paradox for the Kenyan context. Our identification strategy consists of two parts. First of all, we apply multilevel regression models to control simultaneously for family and community clustering of the observed malnutrition and mortality outcomes. Secondly, to address unobserved but correlated factors, we exploit information from GIS and malaria databases to construct variables that capture additional components of children's geographic, political and cultural environment. Our analysis reveals that beneficial agricultural conditions and feeding practices lead to the observed sound anthropometric outcomes around Lake Victoria. In contrast, high mortality rates rest upon an adverse disease environment (malaria prevalence, water pollution, HIV rates) and a policy neglect (underprovision of health care services). Nonetheless, a significant effect of the local ethnic group, the Luo, on mortality remains.
Keywords: I10; I30; O12; R12; 330; child mortality; undernutrition; poverty; multilevel modeling; Sub-Saharan Africa; Kindersterblichkeit; Ernährung; Gesundheitsrisiko; Tropenkrankheit; Gewässerbelastung; AIDS; Armut; Schätzung; Victoriasee; Kenia